Are We There Yet? A Content Analysis of Ability Integrated Advertising on Prime-time TV - Farnall, Olan F.; Lyons, Kelli (Disability Studies Quarterly, 2012)
After more than a decade with no quantitative update on the progress of advertising's integration of disabled characters this study found 29 out of 1,671 prime-time commercials analyzed included images of disability. Although the raw number is only 1.7% of the total sample it represents a 200% increase over 1999 totals. The portrayals were much more likely to be major characters than background roles and the disability depicted in the commercials tended to be from a more diverse set of conditions than it was in the late 1980s. Based on an approximately equal sample of television programming the ability-integrated advertising (AI advertising) appeared more frequently on cable channels (52%) than network channels (39%). Keywords: ability-integrated advertising, content analysis, disability and advertising, SADP